MENINGKATKAN KINERJA PEGAWAI DI LINGKUNGAN RSUD KABUPATEN SERANG - Mastur Mastur; Tika Mariska; Opik Piqhi; Yusuf Riesata; Ranthy Pancasati (J-MACC, 2023)
The reliability of the employees of the Serang District Hospital in terms of the results of the employee's performance. Performance results that prioritize the quality and quantity of their work can increase performance. Employee performance can be increased by placing employees in accordance with the knowledge possessed by employees. Discipline of employees who are able to carry out their duties with agreed procedures is able to elevate employee performance. Compensation given and in accordance with the results of employee performance can elevate employee performance. The research aims to see whether employee performance can be influenced by good placement, increasing discipline, and providing compensation according to work results. The novelty of this study is that placement and compensation are not able to influence employee performance at Serang District Hospital. Research limits itself to employees' assumptions about placement, discipline and placement that have an impact on employee work. The research was conducted on 30 employees of the Serang District Hospital, data collection was carried out by distributing questionnaires which were then analyzed using the Smart PLS method. The results of this study indicate that; 1) Placement has no effect on employee performance, 2) Discipline has an effect on employee performance 3) Compensation has no effect on employee performance.